2018
DOI: 10.1037/xlm0000505
|View full text |Cite
|
Sign up to set email alerts
|

If John is taller than Jake, where is John? Spatial inference from magnitude comparison.

Abstract: We regularly compare magnitudes and describe these comparisons to other people. This article reports 9 experiments that examine how messages about the relative magnitude of two items affect inferences about the items' spatial arrangement. Native English speakers were given sentences such as "One tree is taller than the other," and their beliefs about the left-right arrangement of the objects were probed. Across a wide range of dimensions and tasks, the choice of comparative shaped spatial inference: "Smaller" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…These questions are motivated by a long line of research showing that people internalize and exploit ecological regularities to make inferences when they have incomplete information (e.g., Brunswick, 1943;Gigerenzer et al, 1999;Skylark, 2018), and that recent experience with attribute values and trade-offs shapes the attractiveness of a given option (e.g., Stewart et al, 2003;Tversky & Simonson, 1993;Rigoli & Dolan, 2019). Most pertinent to the current work is a series of studies by Pleskac and colleagues investigating people's expectations about the trade-off between risk and reward.…”
Section: Introductionmentioning
confidence: 99%
“…These questions are motivated by a long line of research showing that people internalize and exploit ecological regularities to make inferences when they have incomplete information (e.g., Brunswick, 1943;Gigerenzer et al, 1999;Skylark, 2018), and that recent experience with attribute values and trade-offs shapes the attractiveness of a given option (e.g., Stewart et al, 2003;Tversky & Simonson, 1993;Rigoli & Dolan, 2019). Most pertinent to the current work is a series of studies by Pleskac and colleagues investigating people's expectations about the trade-off between risk and reward.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the production task, a small-large spatial arrangement of the items led to a weaker HULC effect (i.e., an increase in the tendency to write, for example, "One square is smaller than the other" relative to that seen with a largesmall layout). More recently, Skylark (2018) replicated this effect and also found that message-receivers use the choice of comparative adjective to infer the spatial arrangement of the original items (e.g., "John is taller than Jake" leads to the inference that John was on the left).…”
Section: Introductionmentioning
confidence: 83%
“…The present paper provides a first exploration of this issue. In a series of studies, we had people complete self-report questionnaires to probe traits and states that we thought might be associated with the tendency to choose smaller vs larger comparatives; we probed the latter using the same kinds of language production choice tasks as Matthews and Dylman (2014) and Skylark (2018). Previous research examining individual differences in language use has focussed on freelyproduced text (e.g., by examining people's blog posts or conversations; Mehl, Gosling & Pennebaker, 2006;Yarkoni, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…When people choose before estimating, we suggest that there is a tendency to avoid the ambiguous option purely because it is ambiguous, and that this preference then shapes subsequent explicit estimates of the likely value of the ambiguous attribute. It seems that both preferences and inferences are "constructed" rather than "revealed" (e.g., Skylark, 2018;Slovic, 1995), such that the role of the delay-reward heuristic in choice behaviour depends on the specific conditions under which people are asked to choose.…”
Section: Discussionmentioning
confidence: 99%